3D Hierarchical Core–Shell Nanostructured Arrays on Carbon Fibers as Catalysts for Direct Urea Fuel Cells. Issue 6 (11th October 2017) - Senthilkumar, N.; Gnana kumar, G.; Manthiram, A.
Abstract: Bifunctional cobalt oxide (Co3 O4 ) nanowire catalysts grown on carbon cloth (CC) fibers and their modification with nickel oxide (NiO) and manganese dioxide (MnO2 ) to produce core–shell nanoarchitectures are explored as catalysts for urea oxidation reaction and oxygen reduction reaction in direct urea fuel cells (DUFC). Based on a systematic electrochemical characterization of the catalyst, the as‐developed core–shell nanoarchitectures are optimized toward DUFC performance. Under alkaline conditions with an anion exchange membrane, the DUFC with a cell configuration of Co3 O4 @NiO(1:2)/CC(a|c)Co3 O4 @MnO2 (1:2)/CC exhibits a maximum power density of 33.8 mW cm −2 with excellent durability for 120 h without any performance loss. Furthermore, the DUFC exhibits a maximum power density of 23.2 mW cm −2 with human urine as a fuel. These findings offer an approach to convert human waste into treasure. Abstract : A sustainable energy generation with direct urea fuel cells (DUFC) is demonstrated by utilizing Co3 O4 @NiO and Co3 O4 @MnO2 grown on carbon cloth fibers, respectively, as urea oxidation and oxygen reduction reaction catalysts. The core–shell architecture of the nanocatalysts enables the DUFC to deliver high power density and excellent stability with urea or human urine as fuels.